Familial Dysfibrinogenemia and Thrombophilia - Haverkate, F; Samama, M (Thrombosis and Haemostasis, 1995)
Approximately 250 cases of dysfibrinogenemia have been reported; 55% were asymptomatic (detected by chance), 25% had a tendency to bleeding, and 20% were reported to have a tendency to thrombosis.To establish a possible association between familial dysfibrinogenemia and thrombophilia, data on cases with both affections were collected in a study within the framework of the SSC Subcommittee on Fibrinogen of the International Society on Thrombosis and Haemostasis. Registry forms of 51 cases were received. Twenty-six cases fulfilled the (arbitrarily chosen) criteria of familial dysfibrinogenemia and of thrombosis not due to other causes. Protein C and protein S deficiency and APC resistance as a cause of thrombosis could not be excluded in probands on anticoagulants or investigated before the discovery of the assays.The prevalence of dysfibrinogenemia in patients with a history of venous thrombosis is low, i.e. 0.8%, as deduced from 9 studies in 7 countries on 2376 patients. The 26 cases fulfilling the criteria are characterized by predominantly venous thrombosis at a young age. Severe bleeding was rare and limited to bleeding post partum. Homozygosity was established in 2 cases (Marburg and Naples), hypodysfibrinogenemia (less than 1.5 mg antigen per ml) in 5 cases. A high incidence of problems related to pregnancy, in particular thrombosis post partum and spontaneous abortions was noted amongst the 15 women with thrombophilic dysfibrinogenAn association between dysfibrinogenemia and thrombophilia is indicated by studies on relatives of the 26 probands. Analysis of 187 investigated family members showed that thrombophilia affected 20 persons exclusively in the group of 99 relatives with dysfibrinogenemia, no thrombosis was reported in the group of 88 relatives without the defect. Convincing evidence for such an association became apparent for only 5 individual propositi of whom 2 or more family members had both the defect and thrombotic episodes at a young age (Caracas V, Frankfurt IV/Vlissingen, Melun, Naples and Paris V, also named Dusart).Mainly two mechanisms to explain thrombosis as a consequence of malfunctioning fibrinogen have been suggested: a) A defective binding of thrombin to abnormal fibrin which leads to increased thrombin levels (Malmö, Naples, New York I, Pamplona II, Poitiers), b) A defective stimulatory function of abnormal fibrin in the t-PA mediated fibrinolysis (Argenteuil, Chapel Hill III, Date, New York I, Nijmegen, Pamplona II, Paris V).Defects at the molecular level, elucidated in 15 out of the 26 cases fulfilling the criteria, were localised in the C-terminal part of the γ-chain (3 cases), in the N-terminal part of the Bβ-chain (3 cases) and in the Aα-chain (4 cases) of fibrinogen. Why a particular molecular defect leads to malfunction of fibrin(ogen) is still unknown.